(untitled) (Journal of Partial Differential Equations, 2016)
" By using the method developed in the paper [Georg. Inter. J. Sci. Tech., Volume 3, Issue 1 (2011), 107-129], it is obtained a representation in an explicit form of the weak solution of a linear partial differential equation of the higher order in two variables with initial condition whose coefficients are real-valued simple step functions."